2017
DOI: 10.1002/ejhf.857
|View full text |Cite
|
Sign up to set email alerts
|

Extra corporeal membrane oxygenation in the therapy of cardiogenic shock (ECMO‐CS): rationale and design of the multicenter randomized trial

Abstract: Aims Extracorporeal membrane oxygenation (ECMO) in veno‐arterial configuration represents an increasingly used method for circulatory support. ECMO in cardiogenic shock offers rapid improvement of circulatory status and significant increase in tissue perfusion. Current evidence on the use of ECMO in cardiogenic shock remains insufficient. The aim of the ECMO‐CS trial is to compare two recognized therapeutic approaches in the management of severe cardiogenic shock: early conservative therapy and early implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
(24 reference statements)
0
46
0
1
Order By: Relevance
“…Multiple trials have shown that intra-aortic balloon pump (IABP) counterpulsation provides insufficient support in AMICS to improve survival and therefore many clinicians have opted to use more robust MCS devices such as Impella (Abiomed, Danvers, MA), Tandem Heart (Cardiac Assist Inc, Pittsburgh, PA), and veno-arterial extracorporeal membrane oxygenation (VA-ECMO). [3][4][5][6] In 2016, the Food and Drug Administration (FDA) approved Impella, a percutaneous microaxial MCS device, for use in patients with cardiogenic shock. The basis of Impella's FDA approval and increasing use in the United States has been significant improvements in hemodynamics when compared with IABP.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple trials have shown that intra-aortic balloon pump (IABP) counterpulsation provides insufficient support in AMICS to improve survival and therefore many clinicians have opted to use more robust MCS devices such as Impella (Abiomed, Danvers, MA), Tandem Heart (Cardiac Assist Inc, Pittsburgh, PA), and veno-arterial extracorporeal membrane oxygenation (VA-ECMO). [3][4][5][6] In 2016, the Food and Drug Administration (FDA) approved Impella, a percutaneous microaxial MCS device, for use in patients with cardiogenic shock. The basis of Impella's FDA approval and increasing use in the United States has been significant improvements in hemodynamics when compared with IABP.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MCS implantation including ECMO is allowed in the conservative arm ‘in case of shock progression, i.e. rapid deterioration of haemodynamic or metabolic status (defined as a need for increasing doses of vasopressor or a rise of serum lactate by 3 mmol/L within a minimum of 30 minutes after randomization)’ . The deterioration is only vague and should be more strictly defined, in a way in which no one would dispute the imperative to implant ECMO unless letting the patient die.…”
mentioning
confidence: 99%
“…As previously published, one could imagine a trial of MCS for patients with signs of tissue hypoxia (or arrhythmias) and CRASH score < 0.0375 (a way to reproducibly define refractory CS) in the intervention arm, vs. either no MCS (last resort conception), or very restrictive reproducible criteria (including CRASH score < 0.0300 for example) . In their study, the Authors plan to include severely compromised patients (cardiac index <2.2 L/min/m 2 or systolic blood pressure <100 mmHg, that may be evaluated at about cardiac power index <0.3 W/m 2 ) who do not respond to moderate doses of catecholamine (inotropic score > 15 to >25). Thus they barely aim to maintain CRASH score ≥ 0.06.…”
mentioning
confidence: 99%
See 2 more Smart Citations